On-column internal standardisation as an alternative calibration strategy for speciation analysis: feasibility demonstration through analysis of inorganic As in rice. Issue 33 (30th July 2021) - Petrov, Panayot; Cowen, Simon; Goenaga-Infante, Heidi
Abstract : On-column species-specific internal calibration, based on the injection of internal standard, which is the same as the analyte species, compensates for on-column losses, signal drift and others, and provides accurate measurements with low uncertainty. Abstract : Species-specific isotope dilution mass spectrometry (SS-IDMS) has been the calibration method of choice for high accuracy speciation analysis because it can correct for detector sensitivity drifts, matrix effects, and analyte loss during sample preparation and analysis. However, in many cases SS-IDMS calibration is either not applicable ( e.g. for monoisotopic elements) or not feasible ( e.g. limited by the cost and availability of like-for-like isotopically enriched species). The work presented here demonstrates the potential of a novel on-column species-specific internal calibration approach, which is based on the chromatographic injection of the same species of the analyte as the internal standard (IS), after the sample injection. It can compensate for on-column analyte losses and signal drift and can be applied with any detector capable of recording time-resolved data, provided that enough species resolution can be achieved. The feasibility of this novel calibration strategy for accurate quantitative elemental speciation in complex matrices is demonstrated here through the analysis of inorganic arsenic in rice. An expanded uncertainty ( k = 2) of <10% was obtained for a mass fraction range of 60 to 300 μg kg −1 inorganic-As (i-As) in dry rice products. The method is currently used for the certification of i-As in baby food matrices to support Commission Regulation (EU) 2015/1006 in regard to the maximum levels of i-As in foodstuffs.